Empirically-Derived Subtypes of Lifetime Anxiety Disorders: Developmental and Clinical Correlates in U.S. Adolescents - Burstein, Marcy (2011)
OBJECTIVE: The current study examined the sex- and age-specific structure and comorbidity of lifetime anxiety disorders among U.S. adolescents. METHOD: The sample consisted of 2,539 adolescents (1,505 females and 1,034 males) from the National Comorbidity Survey-Adolescent Supplement who met criteria for DSM-IV lifetime anxiety disorders. Adolescents ranged in age from 13-18 years (M = 15.2 years, SE = 0.08 years) and were 39% non-White. Multiple-group latent class analysis (LCA) was conducted by adolescent sex and age to identify subgroups of adolescents with similar anxiety disorder profiles. Developmental and clinical correlates of empirically-derived classes were also examined to assess the nomological validity of identified subgroups. RESULTS: A seven-class solution provided the best fit to the data, with classes defined primarily by one rather than multiple anxiety disorders. Results also indicated that classes displayed similar diagnostic profiles across age, but varied by sex. Classes characterized by multiple anxiety disorders were consistently associated with a greater degree of persistence, clinical severity, impairment, and comorbidity with other DSM-IV psychiatric disorders. CONCLUSIONS: The presentation of lifetime anxiety disorders among adolescents and the observation of unique correlates of specific classes provide initial evidence for the utility of individual DSM-IV anxiety disorder categories. Although findings of the present study should be considered preliminary, results emphasize the potential value of early intervention and gender-specific conceptualization and treatment of anxiety disorders.